IMPROVING THE METHOD OF FROZEN BERRY PROCESSING IN THE DEVICE WITH VIBRATING PLATE - Sorokopud A.F.; Plotnikov I.B.; Plotnikova L.V. (Техника и технология пищевых производств)
Berries are the most promising source of raw materials for the Siberian region to create products enriched with biologically active substances. Noted are drawbacks of the common method of processing of frozen fruit raw material in the field of low- frequency mechanical vibrations. The expediency of improving its technical and economic characteristics is shown. The experimental device is an apparatus with a diameter of 0.146 m and having a flat bottom. A 3 mm thick flat plate with a diameter of0.142 m and having perforated holes with a diameter of 2.5 ... 3.5 mm is installed in the device. The plate is rigidly fixed on the rod which performs reciprocating motion through a crank mechanism and is connected with the motor shaft. The distance from the plate to the bottom is 0.045 m; the frequency of the plate oscillation is 20 ... 13.3 Hz, and the amplitude of 6, 7 and 8 mm. The device is sealed with a lid which is placed at a distance of 0.02 m from the free surface of the liquid. On the plate periphery a flange is set uniformly upward and downward having the overall height of 0.02 m. The content of dry water-soluble substances is measured with refractometer. Carrying out the experiments we use cranberry collected in 2015 in the Mariinsk district of the Kemerovo region. A 300 gram batch of cranberry frozen at -18°C is placed in a space under and over the plate, 1200 ml of water at the temperature of 18 ± 2°C being poured into the vessel. Then the plate is set in motion. Processing is stopped when equilibrium in the system is reached. Basing on the obtained data the influence of the studied parameters on the extraction of dry water-soluble substances has been established: the diameter of the holes is the most influential parameter while the amplitude of oscillations is less influential but interacting with other parameters it does influence the process. Experimentally-statistical model valid for the studied system in the range of parameter changes has been obtained. The optimization of parameters using Newton's method has been fulfilled. It has been shown that in this case the content of dry substances in the extract increases by almost 2 times in comparison with the known method.